Experimental and topology optimization design study of the shear behaviour of reinforced concrete I-beam web with opening. Issue 9 (2nd September 2022) - Wang, Leijia; Zhu, Mingqiao; Yue, Wenhui; Dong, Jiarui
Abstract : To study the design method of openings on the web of an I-beam, three I-beams with different circular holes were designed using the traditional truss mechanism, and the circular holes were reinforced by ring stirrups. A shear test was performed to study the failure modes of the I-beams and efficiency of the ring stirrups. A new method for establishing the truss mechanism was proposed, which used the windowed evolutionary structural optimization method to calculate the topology optimization solution of the I-beam. From the topology optimization results, the strut-and-tie model (STM) was established, which revealed the stress mechanism of the I-beam. Via the STM, the optimal shape and location for the opening of the I-beam under shear load states were presented. The quantity of reinforcing bars, porosity and ultimate load of the I-beam designed by the STM were, respectively, 0.67, 5.5 and 1.2 times those of the experimental model.